Preparation method of normal-temperature curing high-temperature-resistant thermocouple binder
By using aqueous aluminum phosphate adhesive solution and ceramic powder coated with alkaline metal oxides in the binder, the problem of high curing temperature of existing high-temperature adhesives is solved, and a room-temperature curing and high-temperature durable adhesive is achieved, which is suitable for aircraft heat insulation ground tests.
Patent Information
- Application Number
- CN202411801251.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing high-temperature resistant adhesives have high curing temperatures, making it difficult to effectively cure in aircraft anti-insulated ground tests.
By heating and stirring the aqueous solution of dihydrogen phosphate salt, adding oxalic acid solution, an aqueous solution of aluminum phosphate adhesive is prepared, and alkaline metal oxide is coated in ceramic powder, delaying the reaction speed, reducing the curing temperature, and achieving room temperature curing.
The prepared adhesive can be cured at room temperature, withstand high temperature of 1200℃, and has good insulation performance. It is suitable for the bonding of thermocouples in aircraft anti-insulating ground tests.
Smart Images

Figure CN119614083A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a method for preparing a room temperature curing high temperature resistant thermocouple adhesive. Background Art
[0002] In the ground test of aircraft thermal insulation, quartz lamps are often used to radiate and heat the sample surface, and thermocouples are pasted on the inner and outer surfaces of the sample to test the sample surface temperature. Therefore, the adhesive for bonding the thermocouples is required to have good thermal conductivity, good high temperature resistance, and good insulation to avoid affecting the normal operation of the thermocouples.
[0003] Currently, commonly used high-temperature resistant adhesives generally use silicate adhesives, using chromium oxide or magnesium oxide as a curing agent. The lowest curing temperature of the adhesive is 160°C. However, in aircraft thermal insulation ground tests, the heating and curing conditions of large components are limited, making it difficult to cure the adhesive. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a method for preparing a room temperature curing high temperature resistant thermocouple adhesive to solve the problem of high curing temperature of existing adhesives.
[0005] Based on the above purpose, the present application provides a method for preparing a room temperature curing high temperature resistant thermocouple adhesive, comprising:
[0006] The dihydrogen phosphate aqueous solution is heated and stirred until the solution becomes transparent, and the oxalic acid solution is added and cooled to obtain a viscous aluminum phosphate adhesive aqueous solution;
[0007] The solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder are stirred and mixed, and a supplementing liquid is added dropwise during the stirring process to obtain a mixed liquid, and the mixed liquid is further stirred, aged, filtered, washed and dried to obtain a coated curing agent;
[0008] The filling curing agent and the aluminum phosphate adhesive aqueous solution are stirred and mixed to obtain a room temperature curing high temperature resistant thermocouple adhesive.
[0009] Optionally, the mass ratio of the solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder is (20-50): (20-30): (10-30): (20-50): (1-5): (1-5).
[0010] Optionally, the mass ratio of the solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder is 35:24:17:40:3:2.
[0011] Optionally, the mass ratio of the coating curing agent to the aluminum phosphate adhesive aqueous solution is (2-4):1.
[0012] Optionally, the mass ratio of the coating curing agent to the aluminum phosphate adhesive aqueous solution is (2.5-3.6):1.
[0013] Optionally, the alkali metal oxide is one or more of magnesium oxide, chromium oxide and iron oxide.
[0014] Optionally, the replenishing liquid is a mixture of ethanol and tetraethyl orthosilicate.
[0015] Optionally, the dihydrogen phosphate aqueous solution is an aluminum dihydrogen phosphate aqueous solution with a mass concentration of 50%.
[0016] In the present application, the aluminum phosphate adhesive aqueous solution is used as a base in the preparation of the adhesive to play a bonding role. The prepared adhesive can well bond the thermocouple to the sample surface, wherein the oxalic acid solution is added to prevent the phosphate from dehydrating and recrystallizing;
[0017] In addition, due to the strong activity of alkaline metal oxides, the cross-linking speed with aluminum phosphate adhesives is too fast, which leads to too fast curing speed, and ultimately causes the formation of a loose and porous gel-like structure on the surface of the adhesive, and even fails to form a film. Therefore, the alkaline metal oxide is coated with ceramic powder. The alkaline metal oxide coated with ceramic powder has unevenness and non-compactness. The aluminum phosphate adhesive can slowly enter the interior of the alkaline metal oxide through the gaps and defects of the coating layer, delaying the reaction, increasing the film-forming performance of the adhesive while significantly reducing the curing temperature of the adhesive, and achieving room temperature curing. In addition, the adhesive prepared by coating the alkaline metal oxide with ceramic powder has good insulation performance, preventing thermocouple current leakage, and also has good thermal conductivity, so that the thermocouple can accurately measure the sample temperature.
[0018] Among them, SiO2 generated by the hydrolysis of tetraethyl orthosilicate serves as a connecting skeleton between the ceramic powder and the alkaline metal oxide, so that the ceramic powder can be better coated on the outer wall of the alkaline metal oxide.
[0019] From the above description, it can be seen that the adhesive prepared by the preparation method of the room temperature curing high temperature resistant thermocouple adhesive provided in the present application has a low curing temperature, can withstand high temperatures of 1200°C, has good insulation properties, does not produce irritating odor during coating, and is safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the present application or related technologies, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a physical picture of the mixing, aging and drying of the components of the coating curing agent in Example 1. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0023] It should be noted that, unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0024] Example 1
[0025] The present application provides a method for preparing a room temperature curing high temperature resistant thermocouple adhesive, comprising the following steps:
[0026] S1: Add 100 g of water to 100 g of aluminum dihydrogen phosphate, heat and stir at 100 ° C until dissolved, then the solution is milky white, continue to heat, heat to 150 ° C while stirring, until the solution becomes transparent, add 5 mL of 1% oxalic acid solution, stir evenly, cool to room temperature, and obtain a viscous liquid, which is an aluminum phosphate adhesive aqueous solution;
[0027] S2: Reference Figure 1 , 20 g of ethanol, 20 g of water, 10 g of ammonia water, 20 g of tetraethyl orthosilicate, 1 g of magnesium oxide and 1 g of ceramic powder were mixed and stirred evenly, and a mixed solution of ethanol and tetraethyl orthosilicate in a volume ratio of 1:1 was added dropwise to obtain a mixed solution, and the mixed solution was further stirred, aged, filtered, washed and dried to obtain a coated curing agent;
[0028] S3: 2 g of the coating curing agent and 1 g of the aluminum phosphate adhesive aqueous solution are stirred and mixed to obtain a room temperature curing high temperature resistant thermocouple adhesive.
[0029] Example 2
[0030] The present application provides a method for preparing a room temperature curing high temperature resistant thermocouple adhesive, comprising the following steps:
[0031] S1: Add 100 g of water to 100 g of aluminum dihydrogen phosphate, heat and stir at 100 ° C until dissolved, the solution is milky white, continue to heat, heat to 140 ° C while stirring, until the solution becomes transparent, add 4 mL of 1% oxalic acid solution, stir evenly, cool to room temperature, and obtain a viscous liquid, which is an aluminum phosphate adhesive aqueous solution;
[0032] S2: 20 g of isopropanol, 20 g of water, 10 g of ammonia water, 20 g of tetraethyl orthosilicate, 1 g of iron oxide and 1 g of ceramic powder are mixed and stirred evenly, and a mixed solution of ethanol and tetraethyl orthosilicate in a volume ratio of 1:1 is added dropwise to obtain a mixed solution, and the mixed solution is further stirred, aged, filtered, washed and dried to obtain a coated curing agent;
[0033] S3: 2 g of the coating curing agent and 1 g of the aluminum phosphate adhesive aqueous solution are stirred and mixed to obtain a room temperature curing high temperature resistant thermocouple adhesive.
[0034] Example 3
[0035] The present application provides a method for preparing a room temperature curing high temperature resistant thermocouple adhesive, comprising the following steps:
[0036] S1: Add 100 g of water to 100 g of aluminum dihydrogen phosphate, heat and stir at 100 ° C until dissolved, then the solution is milky white, continue to heat, heat to 160 ° C while stirring, until the solution becomes transparent, add 6 mL of 1% oxalic acid solution, stir evenly, cool to room temperature, and obtain a viscous liquid, which is an aluminum phosphate adhesive aqueous solution;
[0037] S2: 20 g of methanol, 20 g of water, 10 g of ammonia water, 20 g of tetraethyl orthosilicate, 1 g of chromium oxide and 1 g of ceramic powder are mixed and stirred evenly, and a mixed solution of ethanol and tetraethyl orthosilicate in a volume ratio of 1:1 is added dropwise to obtain a mixed solution, and the mixed solution is further stirred, aged, filtered, washed and dried to obtain a coated curing agent;
[0038] S3: 2 g of the coating curing agent and 1 g of the aluminum phosphate adhesive aqueous solution are stirred and mixed to obtain a room temperature curing high temperature resistant thermocouple adhesive.
[0039] Example 4
[0040] The difference between Example 4 and Example 3 is that, in step S2, the amount of methanol added is 50g, the amount of water added is 30g, the amount of ammonia water added is 30g, the amount of tetraethyl orthosilicate added is 50g, the amount of chromium oxide added is 5g, and the amount of ceramic powder added is 5g, and the remaining steps are the same as Example 3.
[0041] Example 5
[0042] The difference between Example 5 and Example 3 is that, in step S2, the amount of methanol added is 35 g, the amount of water added is 24 g, the amount of ammonia water added is 17 g, the amount of tetraethyl orthosilicate added is 40 g, the amount of chromium oxide added is 3 g, and the amount of ceramic powder added is 2 g, and the remaining steps are the same as Example 3.
[0043] Example 6
[0044] The difference between Example 6 and Example 5 is that in step S3, the added amount of the coating curing agent is 4 g, and the remaining steps are the same as Example 5.
[0045] Example 7
[0046] The difference between Example 7 and Example 5 is that in step S3, the added amount of the coating curing agent is 2.5 g, and the remaining steps are the same as Example 5.
[0047] Example 8
[0048] The difference between Example 8 and Example 5 is that in step S3, the added amount of the coating curing agent is 3.6 g, and the remaining steps are the same as Example 5.
[0049] Example 9
[0050] The difference between Example 9 and Example 5 is that in step S3, the added amount of the coating curing agent is 3 g, and the remaining steps are the same as Example 5.
[0051] Comparative Example 1
[0052] The difference between Comparative Example 1 and Example 1 is that the ceramic powder is replaced with an equal amount of graphite powder, and the remaining steps are the same as those of Example 1.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 1 is that ceramic powder is not added in step S2, and the remaining steps are the same as Example 1.
[0055] The detailed parameters of the binders prepared in Examples 1-9 and Comparative Examples 1-2 are shown in the following table:
[0056] Table 1 Detailed parameters of the binders prepared in Examples 1-9 and Comparative Examples 1-2
[0057]
[0058] Performance Testing
[0059] Curing time and apparent performance test: The adhesives prepared in Examples 1-9 and Comparative Examples 1-2 were coated on the sample surfaces respectively, and the curing time of the adhesives was tested according to GB / T 1728-1989 "Determination of Drying Time of Paint Film and Putty Film" and the surface condition of the adhesive layer after surface drying was observed, wherein the curing time is divided into surface drying time and actual drying time, the surface drying time is the time for the surface of the adhesive to dry, and the actual drying time is the time for the inside of the adhesive to dry and solidify;
[0060] Bond strength test: referring to GB / T 31541-2015 "Test method for tensile and shear bond strength of fine ceramic interfaces - cross method", the bond strengths of the adhesives prepared in Examples 1-9 and Comparative Examples 1-2 were examined respectively;
[0061] Temperature resistance test: The adhesives prepared in Examples 1-9 and Comparative Examples 1-2 were coated on different crucibles respectively. After the adhesives were cured, they were calcined at 1200° C. for 5 min in a ceramic muffle furnace, and the surface conditions of the adhesive layers were observed.
[0062] Insulation performance test: A multimeter was used to test the resistance of the cured adhesives prepared in Examples 1-9 and Comparative Examples 1-2.
[0063] The specific test results are shown in the following table:
[0064] Table 2 Comprehensive properties of adhesives prepared in Examples 1-9 and Comparative Examples 1-2
[0065]
[0066] According to Table 2, the adhesive prepared in Examples 1-9 has a surface drying time of 150-210 min, a practical drying time of 600-720 min, a smooth surface after the adhesive is surface dried, no cracks, no bubbles, a bonding strength of more than 7.9 MPa, can withstand a high temperature of 1200° C., a resistance value of more than 1.1 GΩ, good insulation performance and good thermal conductivity, and is suitable for bonding thermocouples;
[0067] Combining Examples 3-5 and Table 2, it can be seen that compared with Example 3, Example 4 has less addition of tetraethyl orthosilicate in Example 4, and SiO2 generated by hydrolysis of tetraethyl orthosilicate can serve as a connecting skeleton between ceramic powder and alkaline metal oxide. Since the amount of tetraethyl orthosilicate added in Example 4 is insufficient, less ceramic powder is coated on the curing agent, which increases the contact between the curing agent and the aluminum phosphate adhesive aqueous solution, resulting in an accelerated curing speed of the adhesive and a reduced bonding strength between the adhesive and the sample; compared with Example 5, Example 3 has a larger amount of ceramic powder added, resulting in excessive coating of the ceramic powder on the curing agent, thereby extending the curing time of the adhesive and increasing the curing time cost of the adhesive. Therefore, in general, the adhesive prepared in Example 5 has better comprehensive performance;
[0068] Combining Examples 5-9 and Table 2, it can be seen that the amount of the aluminum phosphate adhesive aqueous solution added in Example 5 is relatively large, resulting in the prepared adhesive being relatively thin and having good fluidity, making it difficult to apply the adhesive on the sample surface, and increasing the curing time of the adhesive; the amount of the aluminum phosphate adhesive aqueous solution added in Example 6 is relatively small, resulting in the prepared adhesive having poor adhesion and being difficult to be evenly applied on the sample surface. In summary, the adhesives prepared in Examples 7-9 have better comprehensive performance, shorter curing time, and better bonding performance;
[0069] Combining the data of Comparative Example 1 with that of Example 1, it can be seen that compared with the coated curing agent prepared from graphite powder, the adhesive prepared by adding the coated curing agent prepared from ceramic powder to the aluminum phosphate adhesive aqueous solution has good bonding properties and good insulation properties, and is suitable for bonding thermocouple components to avoid affecting the normal operation of the thermocouple.
[0070] Combining the data of Comparative Example 2 with that of Example 1, it can be seen that no ceramic powder was added during the preparation process of Comparative Example 2, resulting in a loose and porous gel-like structure formed on the surface of the prepared adhesive, and the coating was not completely cured in some locations, resulting in poor performance of the adhesive.
[0071] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0072] The embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a room temperature curing high temperature resistant thermocouple adhesive, characterized in that: include: The dihydrogen phosphate aqueous solution is heated and stirred until the solution becomes transparent, and the oxalic acid solution is added and cooled to obtain a viscous aluminum phosphate adhesive aqueous solution; The solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder are stirred and mixed, and a supplementing liquid is added dropwise during the stirring process to obtain a mixed liquid, and the mixed liquid is further stirred, aged, filtered, washed and dried to obtain a coated curing agent; The filling curing agent and the aluminum phosphate adhesive aqueous solution are stirred and mixed to obtain a room temperature curing high temperature resistant thermocouple adhesive.
2. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 1, characterized in that: The mass ratio of the solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder is (20-50): (20-30): (10-30): (20-50): (1-5): (1-5).
3. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 2, characterized in that: The mass ratio of the solvent, water, ammonia water, tetraethyl orthosilicate, alkali metal oxide and ceramic powder is 35:24:17:40:3:
2.
4. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 1, characterized in that: The mass ratio of the coating curing agent to the aluminum phosphate adhesive aqueous solution is (2-4):
1.
5. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 4, characterized in that: The mass ratio of the coating curing agent to the aluminum phosphate adhesive aqueous solution is (2.5-3.6):
1.
6. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 1, characterized in that: The alkali metal oxide is one or more of magnesium oxide, chromium oxide and iron oxide.
7. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 1, characterized in that: The replenishing liquid is a mixed liquid of ethanol and tetraethyl orthosilicate.
8. The method for preparing a room temperature curing high temperature resistant thermocouple adhesive according to claim 1, characterized in that: The dihydrogen phosphate aqueous solution is an aluminum dihydrogen phosphate aqueous solution with a mass concentration of 50%.